The Application of a Deep Learning Strategies in English Language Learning in Indonesia: A Library Research - Pauzan, Pauzan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study examines the Application of deep learning-based teaching strategies in English language learning in Indonesia, aiming to enhance language proficiency and higher-order thinking skills. The approach emphasizes conceptual understanding, critical thinking, and student learning preferences. Strategies explored include Problem-Based Learning (PBL), Project-Based Learning (PjBL), Inquiry-Based Learning (IBL), and Flipped Classroom, which encourage active participation and deeper engagement. Using a qualitative descriptive library research approach, the analysis of relevant literature reveals that deep learning strategies significantly enhance language skills (speaking, writing, listening, reading) by promoting authentic communication and real-world application. Additionally, these strategies foster critical thinking, creativity, and problem-solving abilities, essential for language learners. The findings indicate that deep learning strategies are effective in improving students' language competencies and preparing them for complex real-world challenges. In conclusion, integrating deep learning-based teaching strategies provides an effective approach to improving language proficiency and higher-order thinking skills in English language learning, supporting more meaningful and student-centered learning experiences.